2016
DOI: 10.1093/nar/gkw643
|View full text |Cite
|
Sign up to set email alerts
|

Tunable regulation of CREB DNA binding activity couples genotoxic stress response and metabolism

Abstract: cAMP response element binding protein (CREB) is a key regulator of glucose metabolism and synaptic plasticity that is canonically regulated through recruitment of transcriptional coactivators. Here we show that phosphorylation of CREB on a conserved cluster of Ser residues (the ATM/CK cluster) by the DNA damage-activated protein kinase ataxia-telangiectasia-mutated (ATM) and casein kinase1 (CK1) and casein kinase2 (CK2) positively and negatively regulates CREB-mediated transcription in a signal dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…We next determined whether CREB regulated VE-cadherin transcription and thereby promoted lung endothelial barrier function. CREB is known to bind preferentially the palindromic (TGACGTCA) or half-site (TGAC/G) cyclic AMP response elements (CREs) (18). The 2.5-kb mouse and human VE-cadherin promoter regions contain several of these conserved CREs for CREB binding (Supplemental Figure 2).…”
Section: Creb Regulates Ve-cadherin Transcriptionmentioning
confidence: 99%
“…We next determined whether CREB regulated VE-cadherin transcription and thereby promoted lung endothelial barrier function. CREB is known to bind preferentially the palindromic (TGACGTCA) or half-site (TGAC/G) cyclic AMP response elements (CREs) (18). The 2.5-kb mouse and human VE-cadherin promoter regions contain several of these conserved CREs for CREB binding (Supplemental Figure 2).…”
Section: Creb Regulates Ve-cadherin Transcriptionmentioning
confidence: 99%
“…Three promoter motifs, the TATA box, CCAAT box and the GC box were analyzed. The JASPER CORE 2018 vertebrate library was used to search for transcription factor motifs and several transcriptions factors known to be affected by macronutirent metabolism were analyzed; Atf4 (Averous et al, 2004;Dey et al, 2012), Cebpa (Pedersen et al, 2007), Cebpb (Ramji and Foka, 2002), Creb1 (Kim et al, 2016;Steven et al, 2017), E2f1 (Denechaud et al, 2017), FoxO1 (Kousteni, 2012), Mlx, Mlxip, and Mlxipl (Ma et al, 2006;Havula and Hietakangas, 2012).…”
Section: Promoter Sequences Analysismentioning
confidence: 99%
“…It has since been demonstrated that in response to ROS, ATM phosphorylates downstream targets such as the Chk2 protein kinase and p53 transcription factor [29]. Similarly, CREB is also a direct target for ATM phosphorylation, which serves to regulate CREB-dependent transcriptional activity in response to DNA damage and cellular oxidative stress [30]. In 2010, Guo et al found that ATM is indeed activated in response to oxidative stress in an MRN-independent manner that is separate from its DSB activation [31].…”
mentioning
confidence: 99%